Recent trends in soft beverages - Rao, L. Jagan Mohan; Ramalakshmi, K. (Woodhead Publishing India in food science, technology and nutrition., 2011)
This book discusses recent trends in soft beverages. Chapters discuss chemical composition, health benefits and by-products. Recent trends in value addition are also examined in detail.